Insect Antifeedant and Ixodicidal Compounds from Senecio Adenotrichius - Zuniga-Navarro, G (Wiley-VCH Verlag, 2017)
Nine eremophilane sesquiterpenes 1 – 9, two flavonoids 11 and 12, and two known pirrolizidine alkaloids 13 and 14, were isolated from Senecio adenotrichius DC. Their structures were elucidated on the basis of spectroscopic data and by comparison with previously reported spectroscopic data of similar compounds. Compounds 5, 7, and 9 have not been previously reported as natural products. The antifeedant activity of these compounds was tested against Spodoptera litoralis and Myzus persicae. Eremophilanes 1, 3, and 8 were strong antifeedants to M. persicae, and 1 and 8 to Spodoptera littoralis. Their ixodicidal activity was tested against the tick Hyalomma lusitanicum, with eremophilanes 1, 3, and 8, being strong ixodicidal agents. © 2017 Wiley-VHCA AG, Zurich, Switzerland